Efektivitas Model Pembelajaran Project Based Learning Berbantuan Media Diorama Lapisan Atmosfer terhadap Hasil Belajar Peserta Didik Fase C - Nurul Fitriyani; Siti Patonah; Arfanny Hanum (Journal on Education, 2024)
Quality education must be supported by the selection of appropriate resources and learning models. Focus of the research is to determine effectiveness of the Project Based Learning learning model assisted by atmospheric layer diorama media on the learning outcomes of class V B SDN Peterongan students in Semarang City. Research methods are quantitative. Research is pre-experimental system one group pretest posttest design. Research had a population of 24 students in class V B SDN Peterongan. Saturated samples were used as a sampling technique. Normality, homogeneity, and hypothesis tests are data analysis techniques to be applied when collecting data using SPSS version 2.5. Pretest got an average score of 61.88 and posttest got an average score of 76.67. Based on test results, H0 t-test was rejected and H1 was accepted, because sig (2-tailed) worth 0.000 < 0.05. Research shows results with the emergence of the effectiveness of the use of project-based learning assisted by atmospheric layer diorama media on learning outcomes of phase C students.